Maternal plasma levels of complement Factor H in miscarriage and in normal pregnancy: A cohort study - Savaris, Ricardo Francalacci; Becker, Caroline; Guedes Neto, Ernesto de Paula (Journal of reproductive immunology, 2016)
•We examine if there is an association between CFH and miscarriage.•Median CFH levels were similar between first and second trimester up to 19.6 weeks.•CFH level were not correlated to gestational age.•CFH is not reduced in women with miscarriage, compared to normal pregnancy. The incidence of clinically recognizable miscarriage in general population is up to 15%. It has been shown that complement Factor H (CFH) mRNA levels were increased in endometrium of women during early pregnancy, compared to non-pregnant women. We hypothesized that patients with miscarriage could have lower protein levels of CFH. The objectives of this prospective cohort is to measure plasma levels of Factor H in pregnancies up to 20 weeks, and to investigated whether there is an association between CFH and miscarriage. Plasma levels of CFH were measured in a cohort of pregnant women, ranging from 3 to 19.6 weeks who attended a gynecologic emergency unit in Brazil. Subjects had a blood sample obtained at the first consultation and were followed up to 24 weeks. After reaching outcome, subjects were divided into 4 groups: (1) miscarriage at entry the study, (2) normal pregnancy, (3) those that evolved to miscarriage, and (4) a control group of 6 non-pregnant, fertile proven women. Kruskal–Wallis test was used for statistical analysis. From 193 eligible women, 4 were excluded due technical problems and 33 were lost to follow-up. Median levels (range) of CFH were 989.2μg/mL (372–1644) n=64; 1042μg/mL (600.7–1915) n=74; 1089μg/mL (813.7–1250) n=12; 1004μg/mL (901.7–1335) n=6 in groups 1–3 and control, respectively; p=0.46—Kruskal–Wallis; post-hoc power (1-β)=31.6%. Therefore, median plasma levels of CFH are not different between women with miscarriage or normal pregnancy up to 19.6 weeks.